An exploration of maternity and newborn exposure, training and education among staff working within the North West Ambulance Service. - Heys, Stephanie; Rhind, Susan; Tunn, Joseph; Shethwood, Kate; Henry, John (British Paramedic Journal, 2022)
Aim: Providing emergency and urgent care to pregnant patients and newborns in the prehospital setting often presents some of the most challenging and complex incidents attended to by ambulance staff. A service evaluation survey was undertaken to explore current levels of maternity and newborn education, preferred methods of training delivery, exposure and perceived support surrounding maternity and newborn care provision among pre-hospital clinicians working within the North West Ambulance Service (NWAS) NHS Trust. Methods: An online, anonymised survey compromising of 22 questions using multiple choice options and free-text questions was circulated among NWAS staff between 27 May 2021 and 21 June 2021. Questions explored the levels of training, education, exposure and confidence relating to maternal and newborn care in the pre-hospital setting. Insights into preferred approaches to engaging with continuing professional development (CPD) activities were also captured. Data were analysed using built-in Microsoft Forms analytics for quantitative response, with a basic thematic analysis undertaken to synthesise qualitative responses. Results: The survey received 509 responses, with data providing valuable insight relating to gaps in training provision, preferred approaches to CPD and barriers to engagement. Key themes focused on ‘pre-registration standards and variations’, ‘barriers and facilitators to continuing professional development’ and ‘exposure and skill decline: confidence and knowledge’. Conclusion: Areas for service improvement are highlighted, providing ambulance trusts and integrated care systems with key recommendations. These include maternity and newborn standards for education among paramedic science degree programmes; recognition of pre-hospital emergency maternity and newborn care among maternity providers; the need for exposure and regular multidisciplinary team (MDT) skills training for staff; and a collaborative system-led approach to scaling up and delivering MDT training that acknowledges pre-hospital clinicians as key care providers.